DUKUNGAN KELUARGA BERHUBUNGAN DENGAN KEPATUHAN PERAWATAN DIRI PASIEN ULKUS DIABETIK - Manggasa, Dafrosia Darmi; Rantesigi, Nirva (Universitas Islam Negeri Alauddin Makassar, 2024)
The aim of this study was to analyze the relationship between family support and self-care adherence in diabetic ulcer patients. The research design was a cross sectional study, the sample was 53 diabetic ulcer patients undergoing wound treatment at health service facilities in Poso City. The research results showed that of the 10 respondents (18.9%) who received high family support, 9 respondents (17.0%) were compliant with self-care and 1 respondent (1.9%) was not compliant with self-care. Of the 43 respondents (81.1%) who received low family support, 5 respondents (9.4%) were compliant with self-care and 38 respondents (71.7%) were not compliant with self-care. The results of statistical tests using the Fisher's exact test obtained a p value = 0.000, indicating that there is a significant relationship between family support and compliance with self-care for diabetic ulcer patients. The conclusion is that family support is related to compliance with self-care for diabetic ulcer patients. The higher the family support, the higher the level of compliance with self-care for diabetic ulcer patients, so it is recommended for nurses to educate families to provide support for patients.